2021
DOI: 10.1002/jcb.29896
|View full text |Cite
|
Sign up to set email alerts
|

The role of miR‐29 family in disease

Abstract: MicroRNAs are small noncoding RNAs that can bind to the target sites in the 3’‐untranslated region of messenger RNA to regulate posttranscriptional gene expression. Increasing evidence has identified the miR‐29 family, consisting of miR‐29a, miR‐29b‐1, miR‐29b‐2, and miR‐29c, as key regulators of a number of biological processes. Moreover, their abnormal expression contributes to the etiology of numerous diseases. In the current review, we aimed to summarize the differential expression patterns and functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 246 publications
(320 reference statements)
1
56
0
Order By: Relevance
“…Our data showed that miR-29c deletion induced bone mass loss may be not attributed to adipose differentiation. References identify that miR-29c induced bone loss results from the dysfunction of osteoblast and osteoclast differentiation (Horita et al, 2021), which is consistent with our work.…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed that miR-29c deletion induced bone mass loss may be not attributed to adipose differentiation. References identify that miR-29c induced bone loss results from the dysfunction of osteoblast and osteoclast differentiation (Horita et al, 2021), which is consistent with our work.…”
Section: Discussionsupporting
confidence: 93%
“…Deeper knowledge about the pathophysiological role of CPXM2 in the development of cardiac hypertrophy and fibrosis could help us to implement novel targeted therapies for these conditions. MiRNAs, in general, have been shown to act as potential therapeutic agents [66,67]. For example, Ban et al demonstrated miRNA-497 to accelerate wound healing in diabetic mice after local injection [68].…”
Section: Cpxm2 Expression Is Directly Regulated Via Mir-29b and Via M...mentioning
confidence: 99%
“…The miRNA-29 family includes miRNA-29a, miRNA-29b-1, miRNA-29b-2, and miRNA-29c encoded by genes located on chromosome 7 (7q32.3) and on chromosome 1 (1q32.2). The miRNA-29 family controls cell apoptosis, proliferation, and differentiation and exerts an antifibrotic activity targeting genes concerned extracellular matrix remodelling [39].…”
Section: Mirna-29mentioning
confidence: 99%